Why people comply with COVID-19 social distancing restrictions: Self-interest or duty? - Murphy, Kristina (The Australian and New Zealand journal of criminology, 2020)
On 11 March 2020 the World Health Organization declared the novel coronavirus outbreak (COVID-19) a global pandemic. At the time of writing, over 16 million cases of COVID-19 had been confirmed worldwide, and more than 650,000 people had died from the virus. A priority amongst governments globally is limiting the spread of the virus. In Australia, this response included mandatory ‘lockdown’ restrictions which limited citizens’ freedom of movement. This article uses survey data from 1595 Australians to examine compliance with COVID-19 lockdown restrictions in the early stages of the pandemic. Results revealed that a substantial number of Australians did not comply fully with the measures. Further, while self-interest and health concerns motivated compliance, normative concerns regarding duty to support the authorities dominated compliance decisions. The findings’ implications for both compliance research and for authorities wanting to nurture voluntary compliance with public health orders are discussed.